2014
DOI: 10.5762/kais.2014.15.6.3635
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Self-Directedness, Clinical Practice Experiences and Clinical Practice Satisfaction

Abstract: This study was conducted to describe the relationship of Self-Directedness, Clinical Practice Experience and Clinical Practice Satisfaction of Nursing students. The participants were 223 nursing Students in K City who were surveyed using self report questionnaires from December 5 to December 20 and the data was analyzed using SPSS 20.0. There was a significant positive correlation among Self-Directedness, Clinical Practice Experiences and Clinical Practice Satisfaction. The predictors influencing Clinical Prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…They also had a higher professional self-concept that shows self-esteem as a professional [34]. Cho [35] showed that self-directed students had higher satisfaction with nursing science and clinical practice. These results suggested that nursing activities improving self-directedness needed to be expanded to provide a high satisfaction curriculum to nursing students.…”
Section: The Mediating Effect Of Distress Tolerance and Self-directed...mentioning
confidence: 99%
“…They also had a higher professional self-concept that shows self-esteem as a professional [34]. Cho [35] showed that self-directed students had higher satisfaction with nursing science and clinical practice. These results suggested that nursing activities improving self-directedness needed to be expanded to provide a high satisfaction curriculum to nursing students.…”
Section: The Mediating Effect Of Distress Tolerance and Self-directed...mentioning
confidence: 99%
“…It is difficult even for well-educated nurses to be fully prepared for nursing [ 2 ]. With the recent increase in the awareness of patients’ rights and professional ethics of healthcare professionals, there are limited opportunities for gaining practical experience in real-world clinical settings [ 3 ]. Therefore, changes are needed in nursing education to enable students to acquire the necessary knowledge and skills [ 4 ].…”
Section: Introductionmentioning
confidence: 99%